2021
DOI: 10.1063/5.0035691
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of dopants on acceptor-doped LaMnO3±δ revealed by defect chemistry from first principles

Abstract: Perovskite oxides degrade at elevated temperatures while precipitating dopant-rich particles on the surface. A knowledge-based improvement of surface stability requires a fundamental and quantitative understanding of the dopant precipitation mechanism on these materials. We propose that dopant precipitation is a consequence of the variation of dopant solubility between calcination and operating conditions in solid oxide fuel cells (SOFCs) and electrolyzer cells (SOECs). To study dopant precipitation, we use 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 93 publications
(145 reference statements)
0
5
0
Order By: Relevance
“…The formation of the B-site vacancies ðV 000 Mn Þ under anodic conditions is in line with a recent theoretical and computational work from our group which predicted the formation of a large amount of B-site vacancies in La 0.8 Sr 0.2 -MnO 3 under anodic conditions. 38 In other papers, it was reported that undoped LaMnO 3 contained similar amounts of Aand B-site vacancies under oxidizing conditions, 44,62 and also, some other perovskites are known to exhibit B-site deciency such as Pr 0.5 Sr 0.5 Co 1−y O 3 (10%) 63 and Sr 0.9 La 0.1 Ti 1−y O 3 (6%). 64 Also, we point out the redox-active species on the LCM surface in eqn (3).…”
Section: Mechanism Behind Dopant Re-incorporation Under Anodic Potentialmentioning
confidence: 96%
See 2 more Smart Citations
“…The formation of the B-site vacancies ðV 000 Mn Þ under anodic conditions is in line with a recent theoretical and computational work from our group which predicted the formation of a large amount of B-site vacancies in La 0.8 Sr 0.2 -MnO 3 under anodic conditions. 38 In other papers, it was reported that undoped LaMnO 3 contained similar amounts of Aand B-site vacancies under oxidizing conditions, 44,62 and also, some other perovskites are known to exhibit B-site deciency such as Pr 0.5 Sr 0.5 Co 1−y O 3 (10%) 63 and Sr 0.9 La 0.1 Ti 1−y O 3 (6%). 64 Also, we point out the redox-active species on the LCM surface in eqn (3).…”
Section: Mechanism Behind Dopant Re-incorporation Under Anodic Potentialmentioning
confidence: 96%
“…Mn is thought to be the redox active species in doped LaMnO 3 , 44,65 and we have also assumed that in our previous theoretical work connecting defect reactions to surface segregation. 38 This knowledge comes from bulk defect equilibria studies on the manganite system. 44,65 From the XAS measurements, we found that Mn is indeed redox-active in the bulk, but at the surface it is the lattice oxygen that was redox-active.…”
Section: Mechanism Behind Dopant Re-incorporation Under Anodic Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to Zr and O, this effect is the strongest for Sr, where the elemental profile is even shifted slightly towards the surface, whereas for La and Mn the profiles' points of inflection are shifted towards the bulk region of the complexion. While the general phenomenon of Mn [71][72][73] and Sr [7,[24][25][26][73][74][75][76][77] surface segregation in LSM has been reported for various conditions and doping concentrations, Sr segregation has even been linked to cell performance. [22,23,27,38] Note that this simulation, performed without any polarization and neglecting the oxygen partial pressure, yields the same results as experiments under various experimental conditions.…”
Section: Complexion Surface Terminationmentioning
confidence: 99%
“…The properties of LMO have been studied intensively in the last few years since it was found that the partial substitution of La by Ca, Sr or Ba results in structural changes and the occurrence of colossal magnetoresistance near the temperatures of the spin ordering of Mn ions [2]. Hess et al [3] have studied 20% (Ca, Sr, Ba)-doped LMO using a DFT-based defect chemistry model. Sr substitution at the A-site of LMO nanoparticles could be used for energy applications because it shows a higher current value and higher conductivity, as described by Gupta et al [4].…”
Section: Introductionmentioning
confidence: 99%